2022
DOI: 10.21577/0103-5053.20210163
|View full text |Cite
|
Sign up to set email alerts
|

In vitro Antioxidant and Anticholinesterase Activities of Ouratea fieldingiana (Gardner) Eng. Leaf Extract and Correlation with Its Phenolics Profile with an in silico Study in Relation to Alzheimer’s Disease

Abstract: Ouratea fieldingiana is a native medicinal plant from Northeastern Brazil and many biological properties are due to the phenolic constituents. The objective of this work was performing the characterization of O. fieldingiana leaf constituents to correlate with antioxidant and anticholinesterase activities by in vitro and in silico studies and thus contribute to find new agents against Alzheimer’s disease. The high-performance liquid chromatography revealed the presence of the flavonoids rutin, isoquercitrin, k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 26 publications
(27 reference statements)
1
7
0
Order By: Relevance
“…It is widely used in Chinese medicine and has several biological activities, such as antioxidant, antiinflammatory, antitumor, antimicrobial and healing. These properties make it a potential target for in vivo tests to combat SARS-Cov-2 and memory deficit [5] Our data reinforce the results of previous studies that have identified the presence of flavonoids the rutin, isoquercitrin, kaempferol-3-O-rutinoside and quercetin. [1] Table 1.…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations
“…It is widely used in Chinese medicine and has several biological activities, such as antioxidant, antiinflammatory, antitumor, antimicrobial and healing. These properties make it a potential target for in vivo tests to combat SARS-Cov-2 and memory deficit [5] Our data reinforce the results of previous studies that have identified the presence of flavonoids the rutin, isoquercitrin, kaempferol-3-O-rutinoside and quercetin. [1] Table 1.…”
Section: Resultssupporting
confidence: 89%
“…[31] Although alkaloids are the main targets of research to develop drugs against AD, other compounds are interesting for new studies, such as the flavonoids rutin, isoquercitrin, kaempferol-3-O-rutinoside, quercetin, apigenin and amentoflavone, all of which have high potential for AChE inhibition. [5]…”
Section: Compoundsmentioning
confidence: 99%
See 2 more Smart Citations
“…Frontiers in Nutrition 08 frontiersin.org (30) characterized in vitro cholinesterase inhibition by phenolic compounds from a native medicinal plant in Northeastern Brazil (Ouratea fieldingiana) and two standards (physostigmine and galantamine) were used as the positive controls. The study reported that the IC 50 of the phenolic compounds ranged between 3.12 µg/ml (apigenin) and 12.00 µg/ml (rutin).…”
Section: In Vitro Acetylcholinesterase Inhibitory Activity Of the Syn...mentioning
confidence: 99%